A Simple Link between Hydrocarbon and Borohydride Chemistries. Issue 13 (18th February 2013) - Poater, Jordi; Solà, Miquel; Viñas, Clara; Teixidor, Francesc
Abstract A clear link between the hydrocarbon and borohydride chemistries is established by showing that hydrocarbons and borohydrides have a common root regulated by the number of valence electrons in a confined space. Application of the proposed method to archetypal hydrocarbons leads to well‐known borohydrides but, more importantly, it allows the design of new and interesting boron‐containing molecules that can be a source of inspiration for synthetic chemists.